Results of 12-month rescue treatment with Teduglutide in severely active and parenteral nutrition–dependent Crohn’s disease - Raffaele Borghini; Roberto Caronna; Antonio Picarelli; Enrico S. Corazziari (Turkish Journal of Gastroenterology, 2019)
-